Pengaruh Pemanfaatan Media Sosial dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang - Nurul Yunia Sari; Muhammad Ridwan Basalamah; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to analyze the effect of the use of social media, and entrepreneurial knowledge on the interest in entrepreneurship in students of the Faculty of Economics and Business, Islamic University of Malang, either partially or simultaneously. This study uses a quantitative approach and the type of descriptive research. The population in this study amounted to 830 students with a sample of 89 respondents with the criteria of students from the economics and business faculty of the Islamic University of Malang majoring in management and accounting class 2017 who are active and have businesses, and have taken entrepreneurship courses. Data collection techniques using questionnaires. This study uses multiple linear regression analysis method with the help of SPSS 22 software. The results show that (1) the use of social media and entrepreneurship knowledge has a simultaneous effect on entrepreneurial interest in students of the Faculty of Economics and Business, Islamic University of Malang, (2) the use of social media has a significant effect on entrepreneurial interest in students. Faculty of Economics and Business, Islamic University of Malang. (3) Knowledge of entrepreneurship has a significant effect on interest in entrepreneurship in students of the Faculty of Economics and Business, Islamic University of Malang. Keywords: The use of Social Media, Entrepreneurial Knowledge, Interest in Entrepreneurship